Many-Dimensional Generalized Moment Representations and Padé -Type Approximants for Functions of Many Variables - Holub, A. P.; Голуб, А. П. (Institute of Mathematics, NAS of Ukraine, 2014)
We propose an approach to the construction of multidimensional Pad´e-type approximants for analytic functions based on the extension of Dzyadyk’s method of generalized moment representations.